Crohn's Disease Activity Quantified by Iodine Density Obtained From Dual-Energy Computed Tomography Enterography. Issue 2 (March 2020) - Dane, Bari; Duenas, Sean; Han, Joseph; O'Donnell, Thomas; Ream, Justin; Chang, Shannon; Megibow, Alec
Abstract : Objective: The objective of this study was to assess if bowel wall iodine density obtained from dual-source, dual-energy computed tomography enterography (DECTE) could be a biomarker of Crohn's disease activity. Methods: Twenty-two patients with Crohn's disease imaged with DECTE from February 2016 to May 2018 were retrospectively identified by departmental report search. Iodine maps were created with commercial software (Syngovia). Iodine content was normalized to the aorta, and then manual dual-energy region-of-interest cursors were placed over the visibly assessed maximal and minimal iodine density within segments of involved as well as unaffected small bowel. The mixed Hounsfield unit value, maximum iodine density ( I max ), and minimum iodine density ( I min ) were recorded. The length of affected bowel demonstrating maximum disease activity as a percentage of overall involvement was subjectively assessed. A weighted iodine density ( I weighted ) was calculated. The clinical assessment of disease activity using erythrocyte sedimentation rate, C-reactive protein, fecal calprotectin, colonoscopy/endoscopy, and surgery, if available, served as the reference standard. The Crohn's disease activity index was also used as a separate additional reference standard. Results: Significant heterogeneity within the affected segments was present. The average I max and I min of affected bowel was 4.27 ± 1.11 (2.4–7.4) mg/mL and 2.71 ± 0.51 (2.2–3.9) mg/mL, respectively. Iodine density of normal-appearing small bowel was 1.40 ± 0.26 (0.9–1.9) mg/mL. The I max and I min of affected bowel differed significantly from normal bowel ( P < 0.0001). Mixed Hounsfield unit (101.82 ± 27.5) also statistically differed (46.33 ± 19.62) ( P < 0.0001). Using overall clinical assessment as the reference standard, all patients with I min of greater than 2.6 mg/mL, I weighted of greater than 3.3 mg/mL, or I max of greater than 4.7 mg/mL had clinically active disease. Sixteen of 17 patients with I min of greater than 2.2 mg/mL and 14/15 with I weighted of greater than 3 mg/mL had clinically active disease. Using Crohn's disease activity index as the reference standard, all patients with I min of greater than 2.7 mg/mL, I weighted of greater than 3.6 mg/mL, or I max of greater than 5.4 mg/mL had clinically active disease. The median effective dose was 4.64 ± 1.68 mSv (range, 2.03–8.12 mSv). Conclusions: Iodine density obtained from DECTE highlights regions of maximal activity within affected bowel segments. An iodine density of 2 mg/mL appears to be a threshold between normal bowel segments and those with active Crohn's disease. Iodine density measurement thresholds I min of greater than 2.6 mg/mL, I weighted of greater than 3.3 mg/mL, and I max of greater than 4.7 mg/mL correlate with established clinical markers of disease activity, with I min seemingly most useful in daily clinical practice.